Breast Cancer Risk Factors among Ugandan Women at a Tertiary Hospital: A Case-Control Study - Galukande, Moses; Wabinga, Henry; Mirembe, Florence; Karamagi, Charles (Oncology, 2016)
Although East Africa, like other countries in sub-Saharan Africa, has a lower incidence of breast cancer than high-income countries, the disease rate is rising steeply in Africa; it has nearly tripled in the past few decades in Uganda. There is a paucity of studies that have examined the relation between reproductive factors and breast cancer risk factors in Ugandan women. Objective: To determine breast cancer risk factors among indigenous Ugandan women. Methods: This is a hospital-based unmatched case-control study. Interviews were conducted between 2011 and 2012 using structured questionnaires. Patients with histologyproven breast cancer were recruited over a 2-year period. Logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs). Results: A total of 350 women were recruited; 113 were cases and 237 were controls. The mean age was 47.5 years (SD 14) for the cases and 45.5 years (SD 14.1) for the controls. The odds of breast cancer risk seemed lower for those who breastfed (adjusted OR = 0.04; 95% CI: 0.01, 0.18). There was no significance for early age at first full-term birth (adjusted OR = 1.96; 95% CI: 0.97, 3.96; p = 0.061), and urban residence carried no increased odds of breast cancer either (p = 0.201). Conclusion: Breastfeeding seems to be associated with reduced odds of breast cancer
Keywords: Breast cancer risk factors; Ugandan women; Sub-Saharan Africa